Creative writing in ELT: Organically grown stories - Clarence Ray Bussinger (The Journal of Literature in Language Teaching, 2023)
Many EFL/ESL students do not experience the benefits of practicing creative writing in English, which include expanding knowledge of literature, and using classroom language skills, learning new language structures and vocabulary. Students are motivated to learn English by engaging in creative writing exercises in English language teaching classes. Despite not having the luxury of a creative writing course, it is possible to include such a component in various ESL classes. Following a short discussion of the nature of creative writing and an overview of the relevant research, this article outlines one method of having students produce stories that grow in scaffolded stages, from concept, to words, to lines, then to story. Students report the process to be interesting and non-threatening, and report gains of confidence through sharing their stories